Development of a dietary environmental index to assess nutritional quality versus environmental effect of foods and dietary patterns. (April 2017) - El-Abbadi, Naglaa; Peters, Christian; Griffin, Timothy; Nelson, Miriam; Jacques, Paul
Abstract: Background: Anthropogenic environmental effects of food production and processing, alongside diets that fail to meet nutritional requirements, are contributing to an unhealthy as well as unsustainable food system. Going forward it is crucial that nutritional health be considered alongside the ecological effects of food decisions. However, our ability to assess dietary sustainability is restricted by the absence of coherent, standardised methods that consider both the quality and environmental effects of our diets. As a result, we know little about the sustainability of healthy dietary patterns. Methods: To address this gap, a dietary environmental index (DEX) was developed as an assessment instrument to gauge environmental costs against nutritional quality for foods commonly consumed in the USA. For a nationally representative selection of foods reported in the 2007–08 National Health and Nutrition Examination Survey (NHANES), life cycle assessment (LCA) indicators of land and water resource use, eutrophication, and greenhouse gas emissions were standardised and combined into an aggregate environmental impact score (EIS). The EIS was then evaluated against nutrient density, as determined using the Nutrient Rich Foods Index 9.3, to calculate the DEX values as the ratio of NRF9·3 to EIS for about 1200 NHANES food items arranged into 135 food categories. Findings: DEX scores for most fruit, vegetable, legume, and nut categories performed above the median, and frequently above the 75th percentile, due to simultaneously high NRF9·3 and low EIS. Cereals, pasta, and grain products ranged predominantly around the median DEX. Among dairy, milk and cheeses generally ranked 25th–50th percentile. Meat-based dishes fluctuated around the 25th percentile, with higher DEX generally for poultry and egg products and lower scores for beef and pork. Interpretation: Results obtained from this research will provide insight on how food product choices might enhance the nutritional quality of the diet, while reducing harm to the environment. Funding: The National Institute of Food and Agriculture, US Department of Agriculture and the US Department of Agriculture—Agricultural Research Service (ARS).